Đạo hàm của hàm số $y = \frac{1}{{(x – 1)(x + 3)}}$ bằng biểu thức nào sau đây ?

Đạo hàm của hàm số $y = \frac{1}{{(x – 1)(x + 3)}}$ bằng biểu thức nào sau đây ?.

A. $\frac{1}{{{{(x + 3)}^2}{{(x – 1)}^2}}}$ .

B. $\frac{1}{{2x + 2}}$ .

C. $ – \frac{{2x + 2}}{{{{({x^2} + 2x – 3)}^2}}}$ .

D. $\frac{{ – 4}}{{{{\left( {{x^2} + 2x – 3} \right)}^2}}}$ .

Hướng dẫn giải

Chọn C
Ta có : \[y = \frac{1}{{(x – 1)(x + 3)}} = \frac{1}{{{x^2} + 2x – 3}}\]
$ \Rightarrow y’ = – \frac{{{{\left( {{x^2} + 2x – 3} \right)}^\prime }}}{{{{\left( {{x^2} + 2x – 3} \right)}^2}}} = – \frac{{2x + 2}}{{{{\left( {{x^2} + 2x – 3} \right)}^2}}}.$